Taste and smell disturbances in patients with chronic oral graft vs. host disease: An observational study - Boor, Marlou; Raber-Durlacher, Judith E.; Hazenberg, Mette D.; Rozema, Frederik R.; Laheij, Alexa M. G. A. (Frontiers in Oral Health, 2022)
Background A common complication of allogeneic hematopoietic stem cell transplantation (alloHSCT) is chronic oral graft vs. host disease (cGvHD). Oral cGvHD may present as mucosal lesions, salivary gland dysfunction, and trismus. Moreover, taste and smell ability may be affected, but the prevalence, nature and severity of altered taste and smell function, and their impact on quality of life (QoL) are understudied. Aim To identify the prevalence, nature, and severity of taste and smell disturbances, their impact on QoL and to assess whether altered taste/smell ability is associated with oral mucosal cGvHD or hyposalivation. Materials and methods AlloHSCT recipients at least 100 days post-HSCT and referred for oral cGvHD-related oral complaints were eligible for participation in this cross-sectional study. Manifestations of oral mucosal cGvHD were scored, the (un)stimulated salivary flow was measured, and objective taste and smell ability was evaluated. Subjective taste and smell alterations, and overall and oral health (OH)-related QoL were assessed. Results In total, 45 patients were included, of which objective reduced taste ability (hypogeusia) was identified in 68.9%; 28.9% had reduced smell ability and 11.1% had complete loss of smell. Nevertheless, only 31.1% of patients reported severe taste alterations and 22% reported moderate taste alterations indicating that not all the patients were aware of their altered taste sense. Taste/smell disturbances were not related to oral mucosal cGvHD or hyposalivation. Most alloHSCT recipients reported a decreased OH-related QoL. However, a relation between taste/smell ability and global or OH-related QoL could not be identified. Conclusion Taste and smell disturbances are prevalent among alloHSCT recipients. Most patients reported a decreased OH-related QoL, but the specific impact of taste and smell disturbances remains to be elucidated.